Legal Analysis of Judges' Decisions that do Not Conform to the Values of Justice of the Parties to the Case - Pangestu, Dhea Ramdhani; Endah Wahyuningsih, Sri (UNISSULA Semarang, 2025)
This study aims to analyze what the judges consider in deciding a case in order to be in accordance with the justice values of the parties to the case and the judges' efforts in deciding a case in accordance with the justice values of the parties to the case. This study uses an approachsociological juridical, namely this research only focuses on the results of interviews, in this case it will examine how judges try to decide cases in accordance with the values of justice of the parties to the case.Based on this research, it is concluded that the judge's considerations in deciding the case are considered not in accordance with the values of justice of the parties that we have previously known that in a case there must be evidence that is proven so that the decision meets the values of justice of the parties involved, but there are still some people who think that the judge must be able to decide as fairly as possible but base the decision on the judge's beliefs and the fulfil ment of two pieces of evidence. the judge's efforts in deciding a case in accordance with the values of justice of the parties to the case include firstly upholding procedural law, secondly upholding professional ethics, listening patiently, deciding impartially and considering wisely and using the principle of hearing both parties.